The International Society for the Systems Sciences: Contributions to the Future World - Mobus, George; Sankaran, Shankar; Smith, Gary (European Journal of Social Science Education and Research, 2022)
The International Society for the System Sciences (ISSS) is a microcosm model of the global human social system (HSS, our species). The unprecedented crisis presented by the COVID-19 pandemic is causing major disruptions to the ‘normal’ processes and has triggered a spasm of self-reflection and self-realization that what had been thought of as “the normal” was not sustainable, both for the larger HSS and for the ISSS. Both the greater HSS and the ISSS have had their capacity for resilience in the face of the crisis challenged. Under the proposition that complex adaptive systems are resilient, and evolvable systems are sustainable, members of the ISSS have set out to use our knowledge of systems theory and practice to renew the society, to make it more systemic in structure and function. We are proposing to create a new core working group that will find purpose in doing a dual level deep systems analysis of the ISSS itself and then, using the insights gained in that process, turn to doing the same for the HSS. Deep systems analysis can expose the dysfunctions in subsystems as well as identify missing subsystems and requisite communications. All societies share certain systemic properties since all involve the interactions among groups of human actors. And all long-term sustainable systems have been shown to operate in specific fashions to be self-sustaining (autopoietic) and produce products or services to the larger embedding supra-system. For the HSS this is the Earth as a whole. For the ISSS this is the HSS. Key questions that the ISSS needs to consider as context for its place in the HSS: What product(s)/service(s) should the HSS produce that would benefit the rest of our planet? How should the HSS be structured/organized? The turning that question on the ISSS, what products/services should the ISSS produce that would benefit the HSS. Since the knowledge that is represented within the ISSS pool of expertise is system knowledge, if follows that how the HSS should be structured/organized after the pandemic crisis is in the rearview mirror could be answered by deep systems analysis of what the HSS should be in the future. Key questions to be addressed in this report: With all humbleness how should the ISSS and system societies in general come together to effectively meet the purpose of system science? Indeed, should they and to what purpose? What product(s)/service(s) would the enterprise of system science produce that would benefit the HSS and broader, life on this planet? We report on the plan and the effort undertaken to find answers to these and related questions. This is part of our mission to bring greater unity to the field of systems science and reach out to the wider field of systems thinkers; it is an invitation to participate.
Keywords: Resilience, systems science, systems analysis, organization viability, human social system